Urban Analysis of the Possibility of Building Special Purpose Buildings – Case Study of Air Traffic Control Facility at Nikola Tesla Airport in the City of Belgrade - Lalošević, Marija; Danilović Hristić, Nataša M.; Stefanović, Nebojša (Arhitektura i urbanizam, 2022)
The practice of implementing urban plans for the construction area of the City of Belgrade has shown that in some cases they do not contain enough elements to implement directly. This is especially true for special purpose sites and facilities, whose design and construction require the pre-definition of more detailed conditions and rules of landscaping and construction. In order to address such issues, the authors explore the practice of developing urban analyses in the case of the air traffic control facility at Belgrade’s Nikola Tesla Airport. The paper presents the starting points for developing an urban analysis and excerpts from relevant planning documents, while analyzing the existing condition of the site. The basic results of the analysis show the available capabilities and capacity of the site. In particular, the paper analyzes how well the criteria for building a flight control tower, as a tall object and future location benchmark, were fulfilled. The findings underscore the importance of urban analysis as an instrument for implementing planning solutions for special purpose facilities, which by their nature are unique and of the utmost national importance. The authors also look at urban analysis as a scientific method, while laying out basic guidelines and emphasizing the need for further research.